2011
DOI: 10.1007/s11064-011-0411-8
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic Reticulum Calcium Release Engages Bax Translocation in Cortical Astrocytes

Abstract: Apoptosis is a highly complex form of cell death that can be triggered by alterations in Ca(2+) homeostasis. Members of the Bcl-2 family may regulate apoptosis and modulate Ca(2+) distribution within intracellular compartments. Bax, a proapoptotic member of the family, is constitutively expressed and soluble in the cytosol and, under apoptotic induction, translocates to mitochondrial membranes. However, it is not clear if the intracellular Ca(2+) stores and selective Ca(2+) releases can modulate or control Bax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…In order to induce protein misfolding in the ER, we induced ER stress by using thapsigargin (TG), a well-known agent that mobilizes Ca 2 þ from the ER. 23 As a marker of ER stress we analyzed the expression of BiP/Grp78, a major ER chaperone protein essential for protein quality control in the ER, as well as a central regulator of the UPR. 24 Figure 2 shows that BiP mRNA expression is strongly increased, upon TG treatment, in TRAP1-interfered cells as compared with the respective control (Figures 2a and b).…”
Section: Resultsmentioning
confidence: 99%
“…In order to induce protein misfolding in the ER, we induced ER stress by using thapsigargin (TG), a well-known agent that mobilizes Ca 2 þ from the ER. 23 As a marker of ER stress we analyzed the expression of BiP/Grp78, a major ER chaperone protein essential for protein quality control in the ER, as well as a central regulator of the UPR. 24 Figure 2 shows that BiP mRNA expression is strongly increased, upon TG treatment, in TRAP1-interfered cells as compared with the respective control (Figures 2a and b).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, light irradiation further potentiated the efflux of Ca 2+ from the ER in the presence of TPA-DMPy (Figure E), which was consistent with the cytotoxicity tests (Figure B,D). More importantly, compared to three identified compounds, tetrandrine, thapsigargin, and curcumin, TPA-DMPy induced a higher efflux of Ca 2+ from ER (Figure E).…”
Section: Resultsmentioning
confidence: 93%
“…Our previous work supported the conclusion that alterations in intracellular ER Ca 2+ storage and the selective activation of IP 3 Rs were critical issues in astrocyte cell death (Morales et al ., ; Smaili et al ., ), where Ca 2+ released from IP 3 R selectively induced astrocyte Bax translocation. Indeed, our present results showed that Aβ induces apoptotic cell death in cortical astrocytes in the presence of increased Bax expression and its translocation.…”
Section: Discussionmentioning
confidence: 99%